2002
DOI: 10.1200/jco.2002.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Atrasentan, an Endothelin-Receptor Antagonist for Refractory Adenocarcinomas: Safety and Pharmacokinetics

Abstract: Adverse events were consistent with atrasentan's pharmacologic vasodilatory effect. Linear, dose-proportional pharmacokinetics suggest that atrasentan can be easily and consistently dosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(98 citation statements)
references
References 29 publications
4
92
0
2
Order By: Relevance
“…Previous clinical studies of atrasentan have suggested a mild hemodilution effect as manifested by a decrease in hemoglobin/hematocrit as well as serum albumin and total protein (20,21). In the current study, no statistically significant changes from baseline across all of the dose levels occurred for hemoglobin or hematocrit after 2 or 4 weeks of atrasentan treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous clinical studies of atrasentan have suggested a mild hemodilution effect as manifested by a decrease in hemoglobin/hematocrit as well as serum albumin and total protein (20,21). In the current study, no statistically significant changes from baseline across all of the dose levels occurred for hemoglobin or hematocrit after 2 or 4 weeks of atrasentan treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The frequently observed adverse events of rhinitis, headache, and edema have been reported previously with ET receptor antagonists and are likely attributable to the vasoactive properties of these agents. Data from a previous Phase I study of atrasentan supported 60 mg as the maximum tolerated dose due to increased incidence of headache coincident with higher dose levels (20). Another Phase I study treated patients with doses of up to 95 mg/day without achieving protocol-defined maximum tolerated dose (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, chemical inhibitors of HDACs have been shown to inhibit tumor cell growth and induce differentiation and cell death. [5] Several such inhibitory agents, including suberoyanilide hydroxamic acid (SAHA, aka virinostat) and depsipeptide (FR901228) have reached clinical trials, [6][7][8] and SAHA has been approved by the FDA for use in cutaneous T-cell lymphoma (CTCL). The HDAC inhibitors (HDACIs) also enhance the cytotoxic effects of both radiation and chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Phase I clinical trials suggested a favorable safety profile, and the most common adverse effects were headache, rhinitis, peripheral edema, and asthenia. 11,12 Phase II studies in prostate cancer suggested that atrasentan had modest clinical activity, with statistically significant improvement in time to disease progression, time to prostatespecific antigen (PSA) progression, and changes in bone turnover markers compared with placebo. 9,13 Men with metastatic HRPC treated with placebo exhibited a continued increase in bone alkaline phosphatase (BAP), a marker of osteoblast activity, and N-telopeptide (NTX), a marker of osteoclast activity.…”
mentioning
confidence: 99%